The Influence of the motivational information and behavioral skills (IMB) model on increasing stunting prevention motivation - Darlis, Idhar; Kas, Sri Rezkiani (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Stunting is a chronic nutritional problem in children caused by prolonged inadequate nutritional intake, with long-term negative impacts on their growth and development. The main causes include insufficient nutrition during pregnancy and early childhood, as well as a lack of maternal knowledge about nutrition and limited access to healthcare services and sanitation. Interventions during the First 1000 Days of Life (HPK) are crucial in preventing the rise in stunting rates and the burden it imposes on both society and the government. This study aims to determine the effect of the Information Motivation and Behavioral Skills (IMB) Model on increasing motivation for stunting prevention. Method: This study is a quantitative research using a quasi-experimental approach with a pre-post test design with control group, conducted in Bontomanai Village with 74 respondents divided into two groups: intervention and control. The sample was selected using purposive sampling. The intervention group received treatment using the IMB model through a lecture method, while the control group did not receive any treatment. Data were collected through questionnaires before and after the intervention and analyzed using SPSS with the Wilcoxon test to measure changes in motivation related to stunting prevention behaviors. Results: The study shows that the IMB (Information-Motivation-Behavioral Skills) model has a significant impact on increasing motivation for stunting prevention in Bontomanai Village. In the intervention group, there was a significant increase in motivation from pretest to posttest with a P-value = 0.003, whereas in the control group, the increase in motivation was not significant with a P-value = 0.231. These results confirm the effectiveness of the IMB model in enhancing motivation in the group that received the intervention. Conclusion: This study concludes that the IMB (Information-Motivation-Behavioral Skills) model significantly increases motivation for stunting prevention in Bontomanai Village, as evidenced by the significant statistical results in the intervention group. In contrast, there was no significant change in motivation in the control group, indicating that the IMB model is effective in boosting motivation compared to the group that did not receive the intervention.